Development and assessment of a sugarcane harvesting machine - Ahmed Abdelaty Abdelhady Elnazlawy; Mohamed Mahmoud Ibrahim; Eid Nasr El-Din Abdel rahman; Hany Abdel ghany Mansour; Tharwat Abdel samee Elmesiry (2024)
Manual harvesting of sugarcane requires skilled labourers, as improper harvesting leads to a significant loss of yield. Therefore, it is necessary to move towards developing a system capable of harvesting sugarcane on small holdings, with high harvesting efficiency and evaluated it technically and economically under different operating conditions. This study aims to determine some physical (diameter, length, fresh mass, moisture content MC, true density) and mechanical (compression, shear and bending stress) properties of sugarcane stalks at three moisture content levels (fresh stalk, after 7 days and after 15 from harvesting) and at three positions (base, middle, and top of the stalk) for the following sugarcane varieties (G.T.54-9, IK 76-66, and HAO3-55-24). Results showed that the MC values with different varieties were (70.3, 42.1, and 23.2%), (68.7, 61.3, and 42.7%) and (66.4, 48.6, and 30.5%), respectively. For mechanical properties results showed that by decreasing stalk MC the compression, shear, and bending stresses were increased. A developed sugarcane harvesting machine was fabricated to suit sugarcane (variety G.T.54-9) harvesting in small holdings using two cutting devices (circular saw and a chain saw) at forward speed 0.03, 0.05,0.06, 0.07 km h-1. The machine assessment criteria were the rate of fuel consumption, productivity, field efficiency and the cost of cutting the cane. The results were as follows, increasing the machine cutting speed from 2000 to 3000 rpm tended to increase the fuel consumption rate for circular and chain saw by 52.5 % and 39.8 %, respectively. The cutting productivity of cutting machine with circular saw increased from 3.0, 3.8, 4.3 and 4.7 tons h-1 and for cutting machine with chain saw from 3.1, 4.1, 4.6 and 5.1 tons h-1, by increasing the forward speed from 0.03, 0.05, 0.06 and 0.07 km h-1. The cutting costs of sugarcane crop were 558.9, 489.8 and 3420.1 EGP fed-1 for cutting machine with circular saw, chain saw and manual cutting, respectively. The increase in fatigue rates at the worker$1 (Bs hand, elbow and shoulder by using manual cutting compared with developed machine. s
(3jJWdH GdMUGO GdjOhj dbUH GdScQ YeGdI eGgQI , MjK jDOj GdMUGO ZjQ GdSdje Edi NSGQI cHjQI aj GdeMUhd(B. (3dPdc dG HO ef GdJhLg fMh JWhjQ fXGe bGOQ Ydi MUGO bUH GdScQ aj GdMjGRGJ GdUZjQI hHcaGAI MUGO YGdjI hJbjjeg afjkG hGbJUGOjkG aj Xd XQha JTZjd eNJdaI(B. (3JgOa gPg GdOQGSI Edi JMOjO HYV GdNUGFU GdajRjGFjI (B((3GdbWQ, GdWhd, GdhRf GdWGRL , GdeMJhi GdQWhHj (BMC(3, GdcKGaI GdMbjbjI(B) (3hGdNUGFU GdejcGfjcjI (B((3ELgGO GdVZW hGdbU hGdGfMfGA(B) (3dSjbGf bUH GdScQ YfO KdGKI eSJhjGJ ef GdeMJhi GdQWhHj (B((3GdSGb GdWGRL, HYO (B7 (3CjGe hHYO (B15 (3jhe ef GdMUGO(B) (3haj KdGKI ehGVY (B((3GdbGYOI, hGdhSW, hbeI GdSGb(B) (3dCUfGa bUH GdScQ GdJGdjI (B(G.T.54-9(3, (BIK 76-66(3, h(BHAO3-55-24). (3CXgQJ GdfJGFL Cf bje GdeMJhi GdQWhHj eY GdCUfGa GdeNJdaI cGfJ (B(70.3(3, (B42.1(3, (B23.2%)(3, (B(68.7(3, (B61.3(3, (B42.7 %) (3h (B(66.4(3, (B48.6(3, (B30.5 %)(3, Ydi GdJhGdj(B. (3HGdfSHI ddNUGFU GdejcGfjcjI, CXgQJ GdfJGFL Cfg ef NdGd Jbdjd GdeMJhi GdQWhHj ddSGb , jJe RjGOI GLgGOGJ GdVZW hGdbU hGdGfMfGA(B. (3Je JUfjY hJWhjQ BdI dMUGO bUH GdScQ dJfGSH MUGO SjbGf bUH GdScQ (B((3Ufa (BG.T.54-9) (3aj GdeRGQY GdUZjQI HGSJNOGe SdGMi bWY (B((3efTGQ OGFQj hefTGQ LfRjQi(B) (3YfO GdSQYGJ GdCeGejI (B0.03 (3, (B0.05 (3, (B0.06 (3, (B0.07 (3ce(B/(3SGYI(B. (3hcGfJ eYGjjQ Jbjje GdGdI gj eYOd GSJgdGc GdhbhO, hGdEfJGLjI, hGdcaGAI GdMbdjI, hJcdaI bWY GdbUH(B. (3hcGfJ GdfJGFL cGdBJj(B: (3RjGOI SQYI bWY GdGdI ef (B2000 (3Edi (B3000 (3daI aj GdObjbI COJ Edi RjGOI eYOd GSJgdGc GdhbhO ddefTGQ GdOGFQj hGdefTGQ GdLfRjQj HfSHI (B52.5% (3h(B39.8% (3Ydi GdJhGdj(B. (3RGOJ EfJGLjI GdbWY dBdI GdMUGO HGdefTGQ GdOGFQj ef (B3.0(3, (B3.8(3, (B4.3 (3h(B4.7 (3Wf(B/(3SGYI hdBdI GdMUGO HGdefTGQ GdLfRjQj ef (B3.1(3, (B4.1(3, (B4.6 (3h(B5.1 (3Wf(B/(3SGYI, ef NdGd RjGOI GdSQYI GdCeGejI ef (B0.03(3, (B0.05(3, (B0.06 (3h (B0.07 (3ce(B/(3SGYI Ydi GdJQJjH(B. (3HdZJ JcdaI GdMUGO deMUhd bUH GdScQ(B558.9 (3, (B489.8 (3, (B3420.1 (3LfjgkG eUQjkG (B/ (3ddaOGf dBdI GdMUGO Ph GdefTGQ GdOGFQi hGdBdI Ph GdefTGQ GdLfRjQi hGdbWY GdjOhi Ydi GdJQJjH(B. (3jROGO eYOd GdGLgGO GdYVdi GdhGbY Ydi jO hchY hcJa GdYGed HGSJNOGe GdMUGO GdjOhi ebGQfI HGSJNOGe GdGdI GdeWhQI(B.s
Thesis (Ph.D)-Cairo University, 2024.
Bibliography: pages 164-182.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Sugarcane; Sugarcane -- mechanical harvest -- stalk -- muscle fatigue -- machine performance